Blogging in Beirut: An Ethnography of a Digital Media Practice - Jurkiewicz, Sarah (transcript, 2018)
Unlike previous media-analytic research, Sarah Jurkiewicz's anthropological study understands blogging as a social field and a domain of practice. This approach underlines the significance of blogging in practitioners' daily lives and for their self-understanding. In this context, the notion of publicness enables a consideration of publics not as static 'spheres' that actors merely enter, but as produced and constituted by social practices. The vibrant media landscape of Beirut serves as a selection of samples for an ethnographic exploration of blogging.